Women and the decade of commemorations - Frawley, Oona (Irish culture, memory, and place., 2021)
"When women are erased from history, what are we left with? Between 1912 and 1922, Ireland experienced sweeping social and political change, including the Easter Rising, World War I, the Irish Civil War, the fight for Irish women's suffrage, the founding of the Abbey Theatre, and the passage of the Home Rule Bill. In preparation for the centennial of this epic decade, the Irish government formed a group of experts to oversee the ways in which the country would remember this monumental time. Unfortunately, the group was formed with no attempt at gender balance. Women and the Decade of Commemorations, edited by Oona Frawley, highlights not only the responsibilities of Irish women, past and present, but it also privileges women's scholarship in an attempt to redress what has been a long-standing imbalance. For example, contributors note the role of the Waking the Feminists movement, which was ignited when, in 2016, the Abbey Theater released its male-dominated centenary program. They also discuss the importance of addressing missing history and curating memory to correct the historical record when it comes to remembering revolution. Together, the essays in Women and the Decade of Commemorations consider the impact of women's unseen, unsung work, which has been critically important in shaping Ireland, a country that continues to struggle with honoring the full role of women today"--